Effect of Physiotherapy on the Motor Recovery and Improvement in Patients with Facial Palsy - Bader, baida (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: The study aims to investigate the efficiency of physiotherapy methods to improve the degree of the clinical recovery of the peripheral facial palsy. Methodology: This study is carried out at the Rehabilitation Center-Baghdad from November 2009 till March 2010. This study includes (40) patient, their ages are from (13) to (55) years old; (24) male and (16) female with unilateral facial palsy of undetermined cause. House-Brackmann facial recovery scores have been used before and after the physiotherapy treatment. Results: The results show that the physiotherapy sessions obtained the best effect of the electrical stimulation, exercises and massage in the treatment of facial palsy. Highly respondents in females compared to males in the total improvement, highly respondents in partial recovery compared to total recovery. Recommendations: The study recommends that the physiotherapists and patients should use the physiotherapy sessions with follow-up that include stimulation, massage and exercises and complete all sessions of treatment.